Finite cyclic q-group’s automorphisms with qr-generator - Fatin Hanani, Hasan; Mohd Sham, Mohamad; Yuhani, Yusof; Nor Amirah, Mohd Busul Aklan; Siti Hasanah, Jusoo; Sangwisut, Ekkasit (Penerbit UMP, 2024)
The finite cyclic q-group, where q being odd prime, requires generators to validate the formation of automorphisms. A summary of cyclic groups, automorphisms, and characteristics is provided as a foundation for this research. By evaluating the automorphisms, the generators for the qr -power cyclic group in their specific sequence have been uncovered and presented as the key finding.